Estudio del potencial probiótico de lactobacilos aislados de fuentes naturales - Zamudio., Karin L. (2003)
The use of the lasctobacilos as probiotics has been increased due to its beneficial properties for the human and animal health. With the objective to identify and to obtain native starais of lactobacilos to be used as probiotics , 9 isolated lactobacilos from different natural sources were selected. The Lactobacillus species were identified by carbohydrate fermentation patterns and by the Polymerase Chain Reaction using specific primers designed from 16S-23S rDNA intergenic spacer regions. The selected lactobacilos belong to the following species: Lactobacillus plantarum, Lb acidophilus, Lb. casei and Lb. fermentum corresponding in number of strains by species 3, 3, 2 and 1 respectively. The probiotic potential of these microorganismos was determined by low pH stability, tolerance to bile and their antimicrobial activity against the enteric pathogens Listeria monocytogenes and Escherichia coli, Lb acidophilus 4P-1 showed the best probiotic characteristics to resist more than 24 hours at pH 3,5 and to inhibit pathogens mentioned above.